1997
DOI: 10.1002/clc.4960200914
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of blood row distribution to exercising and resting skeletal muscles in patients with cardiac dysfunction using whole‐body thallium‐201 scintigraphy

Abstract: SummaryBuckground and hypothesis: Decreased blood flow to working muscles makes an important contribution to exercise intolerance in patients with chronic heart failure. This study was undertaken to examine whether maldistribution of skeletal muscle blood flow is closely related to exercise intolerance in patients with cardiac dysfunction.Methods: Whole-body thallium scintigraphy was perfomed during one-leg exercise in 11 patients with left ventricular (LV) dysfunction (LV ejection fraction ~4 5 % ) .Blood flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Vascular resistance in the muscle fails to decrease normally during exercise in patients with HF, and flow to the nonexercising tissues may be preferentially maintained at the expense of hypoperfusion in the exercising muscle. 20,49 Ergoreflex Activation A new paradigm suggests the presence of a specific signal arising from the exercising muscle (possibly including respiratory muscle) that is abnormally enhanced in HF. 50,51 These signals contribute to the abnormal hemodynamic, autonomic, and ventilatory responses to exercise that characterize HF.…”
Section: Distribution Of Cardiac Outputmentioning
confidence: 99%
“…Vascular resistance in the muscle fails to decrease normally during exercise in patients with HF, and flow to the nonexercising tissues may be preferentially maintained at the expense of hypoperfusion in the exercising muscle. 20,49 Ergoreflex Activation A new paradigm suggests the presence of a specific signal arising from the exercising muscle (possibly including respiratory muscle) that is abnormally enhanced in HF. 50,51 These signals contribute to the abnormal hemodynamic, autonomic, and ventilatory responses to exercise that characterize HF.…”
Section: Distribution Of Cardiac Outputmentioning
confidence: 99%
“…Central factors Sullivan and Cobb [52] Cardiac Lower max HR and SV Stevenson et al [53] Vascular Elevated SVR Lung factors Guazzi [54] Diffusion impairment Alveolar-capillary membrane disruption Mancini et al [55] Respiratory muscle function Histologic changes Peripheral factors Zelis et al [56] Abnormalities in blood flow Lower vasodilatation Drexler and Lu [57] Endothelial function Lower NO release Floras [58] Autonomic changes Increased SNA, RAS Skeletal muscle Massie et al [59] Metabolism Early anaerobic Drexler et al [60], Sullivan et al [61] Composition Increased type IIB and lower I fibers Sullivan et al [62] Enzyme Lower oxidative Gielen et al [32], Vescovo et al [63] Inflammation Increased cytokines, apoptosis Wada et al [64] Distribution of cardiac output Lower muscle blood flow Ponikowski et al [8], Piepoli et …”
Section: Study Factors Mechanismsmentioning
confidence: 99%
“…Indirect support to this hypothesis in humans has been given by O'Donnell and coworkers (39) who found that the improvement in exercise endurance with pressure support ventilation was associated with less exertional leg discomfort in patients with CHF. In addition, skeletal muscle perfusion has been shown to be selectively reduced as whole body exercise progresses in some patients with CHF (34,53); this effect, however, was not found with small muscle mass exercise where the ventilatory requirements are considerably lower (27). There is, therefore, a sound rationale underpinning the notion that respiratory and peripheral muscles could actively compete for the available cardiac output (Q T ), especially in pathological conditions where the ability to further increase O 2 delivery is impaired.…”
mentioning
confidence: 99%